A new species of Rhigognostis (Lepidoptera, Plutellidae) from the Canary Islands - Baraniak, Edward; Larsen, Knud; Kubasik, Wojciech; Grzegorczyk, Tomasz (Zootaxa, 2017)
Rhigognostis canariella sp. nov. is described from the Canary Islands on the basis of five females. The morphological micro structures of the female genitalia are figured. An illustrative diagnostic summary for three allied congeners, R. annulatella(Curtis, 1832), R. kovacsi (Gozmány, 1952) and R. schmaltzella (Zetterstedt, 1839) is provided.